2011
DOI: 10.1007/s00464-011-1671-8
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneoscopic lumbar sympathectomy: prospective study upon a series of 50 consecutive patients

Abstract: For a larger number of cases, retroperitoneal LS has been proven effective and safe in PAOD beyond reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…LS is a typical procedure for treating arterial occlusion of the lower limbs. However, its long‐term effects are limited (Nemes et al, 2011; Ruiz‐Aragon & Calderon, 2010), possibly because VBs innervate the lower limb arteries from two groups of nerves: the lumbar sympathetic trunk and the lumbosacral plexus. Moreover, LS cannot block the VBs from the lumbosacral plexus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LS is a typical procedure for treating arterial occlusion of the lower limbs. However, its long‐term effects are limited (Nemes et al, 2011; Ruiz‐Aragon & Calderon, 2010), possibly because VBs innervate the lower limb arteries from two groups of nerves: the lumbar sympathetic trunk and the lumbosacral plexus. Moreover, LS cannot block the VBs from the lumbosacral plexus.…”
Section: Discussionmentioning
confidence: 99%
“…VBs originating from the lumbar sympathetic trunk are frequently removed to relieve pain or salvage limbs when treating nonreconstructable critical lower limb ischemia (CLLI) caused by peripheral arterial occlusive disease (Batca et al, 2011; Karanth et al, 2016). Studies have shown that lumbar sympathectomy (LS) has a better early effect in the treatment of lower limb arterial occlusive disease, but the limb salvage rate in the second postoperative year is lower than that in the first year postoperatively (Nemes et al, 2011). A retrospective study showed no difference in the efficacy between surgical and medical treatment for the occlusive peripheral arterial disease of the lower limbs (Ruiz‐Aragon & Calderon, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…75% of vascular surgical society members in UK and Ireland still continue to use lumbar chemical sympathectomy in their practice. [6][7][8] Many studies have documented the efficacy of CT guided lumbar sympathectomy in treating severe rest pain due to inoperable peripheral vascular disease. In a recent study by Florek R et al, 80% showed significant improvement at 3 months which correlated with our study.…”
Section: Discussionmentioning
confidence: 99%
“…The first, erection, is a response mediated predominantly through the parasympathetic nervous system by the pelvic splanchnic nerves (nervi erigentes) arising from segments S2, S3, and S4 ( Fig. 50 The second component, ejaculation, can be divided into two phases. Activation of these nerves causes vasodilatation and engorgement of the penile musculature and sinuses.…”
Section: Disorders Of Sexual Functionmentioning
confidence: 99%